Analysis of Judges' Decisions in Marriage Isbat Cases According to the Perspective of Positive Law and Islamic Law (Case Study No.076/Pdt.P/2022/Pa.Prob) - Sigit Siswomiharjo; Abu Yazid Adnan Qutni; Imam Syafi’i (Al Mashaadir : Jurnal Ilmu Syariah, 2023)
Isbat marriage is a determination of the validity of a marriage that is determined by a religious court. Marriage that is consecrated is a marriage that is legally religious but not yet legal by the state. So that the marriage does not get legal certainty. So not a few people do isbat marriage as aform of effort to get legal certainty for the marriage they do. This study reviews the cases of marriage constituencies that are still rife in Probolinggo district. Whith the focus of research namelly the results of the analysis of the judge’s decision at the Probolinggo religious court in accepting, analyzing, determining, and deciding cases of marriage registrations the analysis in question uses to two approaches, namely the perspektif of positif law and islamic law. Marriage isbat cases are cases is ranked number two after divorce cases filed by the local community. From the data the author obtained between 2021 and 2022 there were as many as 41 cases of marriage confirmation recaived by the religious courts. Marriage confirmation both in the perspektive of positif law and islamic law thend, beering in mind that marriage confirmtion is still wideli practiced, unfortunately, the party filing this case is the perpetrathor of the sirri marriage, the author want to make it clear to society in general that marriage confirmation is a matter that is as far as possible be used as the final step in completing siri marriage get vallidity of the marriage they do. This means that the marriage certificate is solely carried out because it is a necessity, not to legalize a sim marriage. The law specifically limits marriage isbat only to a number of urgent matters, primary by conducting interviews with the chief judge, deputy chief judge, and information desk officer. Meanwhile secondary data comes from reference to journals, scientific books and data reports at the Probolinggo religious court. Data collections tecniques include observation, interviews, and documentation.